Pengaruh Model Project Based Learning Berbasis Video Terhadap Hasil Belajar IPS Murid Kelas IV UPTD SD Negeri 44 Barru - Sulvahrul Amin; Yumriani Yumriani; Randi Randi (LPPM Politeknik Pratama, 2024)
The problem of low student learning outcomes in Social Science Subjects is caused by less active students in the learning process, besides that it is caused by learning Social Sciences is still teacher centered, so student learning outcomes are low. The formulation of the problem in this study is the Effect of Video-Based Learning Projed Based Model on Social Studies Learning Outcomes of Class IV Students in the even semester at UPTD SD Negeri 44 Barru for the 2023/2024 academic year? This study aims to determine Projed Based Learning on social studies learning outcomes of grade IV students of UPTD SD Negeri 44 Barru. This type of research is Experiment. The data collection tools used are tests, and documentation. The research instrument uses an essay test that matches the indicators. Based on the results of the study, it is known that learning using the Projed Based Learning learning model obtained tCalculate = 34.013 and tTable = 1.724 then obtained tCalculate > tTable or 34.013> 1.724. So it can be concluded that H0 is rejected and H1 is accepted. This means that the use of the Pro learning model Projed Based Learning affects social studies learning outcomes.